Treatment and Survival Outcomes of Waldenstrom Macroglobulinemia in Latin American Patients: A Multinational Retrospective Cohort Study - Riva E (2022)
PURPOSE: Waldenstrom Macroglobulinemia (WM) is a rare lymphoma with distinct clinical features, and data from Latin American patients are lacking. Therefore, we aim to investigate the clinical, therapy, and outcome patterns of WM in Latin America. METHODS: We retrospectively analyzed patients with WM diagnosed between 1991 and 2019 from 24 centers in seven Latin American countries. The study outcomes were overall survival (OS) and progression-free survival (PFS). RESULTS: We identified 159 cases (median age 67 years, male 62%). Most patients (95%) were symptomatic at diagnosis. The International Prognostic Scoring System for WM (IPSSWM) at diagnosis was available in 141 (89%) patients (high-risk 40%, intermediate-risk 37%, and low-risk 23%). Twenty-seven (17%) patients were tested for MYD88L265P, with 89% (n = 24 of 27) carrying the mutation. First-line and second-line therapies were administered to 142 (89%) and 53 (33%) patients, respectively. Chemoimmunotherapy was the most commonly used first-line (66%) and second-line (45%) approach